2017
DOI: 10.1103/physrevc.95.045805
|View full text |Cite
|
Sign up to set email alerts
|

La137,138,139(n,γ) cross sections constrained with statistical decay properties of et al.

Abstract: The nuclear level densities and γ-ray strength functions of 138,139,140 La were measured using the 139 La( 3 He, α), 139 La( 3 He, 3 He ′ ) and 139 La(d, p) reactions. The particle-γ coincidences were recorded with the silicon particle telescope (SiRi) and NaI(Tl) (CACTUS) arrays. In the context of these experimental results, the low-energy enhancement in the A∼140 region is discussed. The 137,138,139 La(n, γ) cross sections were calculated at s-and p-process temperatures using the experimentally measured nuc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 58 publications
1
30
0
Order By: Relevance
“…Similar results have been observed in Ref. [10], where different normalization models and spin distributions were explored in detail, yielding the same results. The agreement further validates that experimental NLDs and γ SFs can be used to obtain (n, γ ) cross sections indirectly and gives confidence in this technique to determine reliable (n, γ ) cross sections for which (d, p) 182 Ta reaction, compared to previous measurements [59][60][61].…”
Section: Nucleussupporting
confidence: 88%
See 1 more Smart Citation
“…Similar results have been observed in Ref. [10], where different normalization models and spin distributions were explored in detail, yielding the same results. The agreement further validates that experimental NLDs and γ SFs can be used to obtain (n, γ ) cross sections indirectly and gives confidence in this technique to determine reliable (n, γ ) cross sections for which (d, p) 182 Ta reaction, compared to previous measurements [59][60][61].…”
Section: Nucleussupporting
confidence: 88%
“…Hence, NLD and γ SF are nuclear properties of significance to nucleosynthesis [7] and calculations have shown that relative small changes to the overall shape of the γ SF, such as a pygmy resonance, can have an order-of-magnitude effect on the rate of elemental formation [8]. It has been shown that measured statistical properties can reliably be used to reproduce capture cross sections that were measured using other techniques [9][10][11], although further validations are needed across the nuclear chart. Additionally, NLD and γ SF can also be relevant to the design of existing and future nuclear power reactors, where simulations depend on such nuclear data [1].…”
Section: Introductionmentioning
confidence: 99%
“…Note that the dipole strength data extracted from the Oslo method only include experimental systematic uncertainties and not model-dependent statistical uncertainties which can be significantly larger and even change the slope of the dipole strength (see Refs. [49,50] for more details). The low-energy tail of the dipole strength is seen to be globally fairly well reproduced.…”
Section: Comparison With Experimentsmentioning
confidence: 99%
“…For instance, it has been shown that the presence of a Pygmy resonance [7] or an enhanced low-energy γ-ray decay probability [13] can lead to order of magnitude deviations on the capture cross sections for nuclei that undergo the rapid neutroncapture process [14]. The γSF and NLD have been shown to reliably reproduce results from directly measured (n, γ) [15,16] and (p, γ) [17] cross sections. Direct measurements are limited to reasonably long-lived targets and hence statistical properties will play an increasingly important role in determining many astrophysically relevant cross sections.…”
Section: Introductionmentioning
confidence: 99%